Proposal of a framework of available digital tools for the research project “Simulación virtual en 3D para el aprendizaje del francés con objetivos específicos-francés de negocios” (2017)
Due to the need that there are in the students of ECCI university in the Modern languages program for finding a tool to study French language focused on business It has executed a proposal to create a virtual simulation in 3D. In order to analyze the current options for learning French that are on the digital market and to evaluate the strengths and failures of them, there has been realized a study that has showed that there are very few support tools for the students, since many of them do not focus on business French and some are difficult and expensive to access. Bearing in mind this information it tries to contribute to the ideal achievement of the prototype of virtual simulation in 3D to business French.